LEUKEMIC PHASE OF MALIGNANT LYMPHOMA IN CHILDREN - Sahriany S; Agus Alim Abdulah; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Leukemic phase of malignant lymphoma is a group of lymphoid malignancies typically localized in lymph node and present typical clinical features such as lymphadenopathy with irregular distribution. It can manifest as an extranodal disorder infiltrates the bloodstream (leukemic phase). Lymphomas are differentiated into Hodgkin and non-Hodgkin. The presentation of Reed-Sternberg (RS) cells in histological evaluation establishes Hodgkin lymphoma. A number of classification systems have been used before the publication of Revised European American Lymphoma (REAL) classification in 1994 which includes all lymphoid and lymphoma malignancies according to typical histology, morphology, immunophenotype, genetic, and clinical manifestation. A highly proliferative and fatal malignant lymphoma with leukemic phase case in 13 years and a one-month-old male was reported. The diagnosis was established based on marble-sized lymph nodes enlargement that increased in size, two weeks after initial identification on the neck, head, and inguinal regions and followed by lymphadenopathies in submental, right submandibular, preauricular and right inguinal region. No fever history of this patient or malignant history among his family was found. Laboratory findings included WBC of 26,050/µL, Hb 9.6 g/dL, and PLT 16,000/µL. Peripheral blood smear results indicated suspected leukemic phase of malignant lymphoma DD/ALL. Bone marrow aspiration showed leukemic-phase of malignant lymphoma with bone marrow infiltration. Cytological evaluation of Fine Needle Aspiration (FNA) identified atypical round nucleated cells with nucleus size mostly larger than the mature lymphocytes, minimum cytoplasm, diffuse erythrocyte as background, a conclusion was malignant lymphoma.